Modeling the CD95 receptor mediated pathway of apoptosis using stochastic Pi-calculus - Yap, Jan Michael C. (2007)
Apoptosis is a morphological processes that follows a sequence of controlled steps leading to locally and temporally defined controlled cellular self-destruction. Understanding the dynamics of such process is vital in the medical field as evidenced particularly by its correlation with the study of cancer. In this work, we proposed a stochastic pi-calculus representation of a receptor mediated apoptosis. In particular, we used the structured information model of the CD95-induced apoptosis including the parameters as reported by the group of Bentele in 2004. We provided qualitative and quantitative analysis of the model. Reachability and specification matching reveal that the representation is consistent. Quantitatively, our simulations were found to be consistent with the expected behavior. The representation provided more details exhibited in the simulation results. We used the SPiM software for the simulations and analysis.
Thesis (M.S. Computer Science)--University of the Philippines Diliman.
Keywords: Apoptosis; Pi-calculus.